2012
DOI: 10.1111/j.1440-1681.2012.05704.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteins within the intracellular calcium store determine cardiac RyR channel activity and cardiac output

Abstract: The contractile function of the heart requires the release of Ca(2+) from intracellular Ca(2+) stores in the sarcoplasmic reticulum (SR) of cardiac muscle cells. The efficacy of Ca(2+) release depends on the amount of Ca(2+) loaded into the Ca(2+) store and the way in which this 'Ca(2+) load' influences the activity of the cardiac ryanodine receptor Ca(2+) release channel (RyR2). The effects of the Ca(2+) load on Ca(2+) release through RyR2 are facilitated by: (i) the sensitivity of RyR2 itself to lum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 62 publications
(161 reference statements)
2
35
0
Order By: Relevance
“…3F) is also consistent with the increase in Ca 2+ -binding sites within the store provided by CSQ2, indicating that more time is required to reach a high-enough level of free luminal Ca 2+ to trigger the next Ca 2+ -release event (Jiang et al, 2002). In addition, it has been reported that although RyR2 activity decreases when CSQ2 is dissociated (Wei et al, 2009), the relative open probability increases more steeply with luminal Ca 2+ after CSQ2 dissociation (Dulhunty et al, 2012), in agreement with our findings that the rate of spontaneous Ca 2+ release is increased in the absence of CSQ2 (Fig. 3C).…”
Section: Resultssupporting
confidence: 93%
“…3F) is also consistent with the increase in Ca 2+ -binding sites within the store provided by CSQ2, indicating that more time is required to reach a high-enough level of free luminal Ca 2+ to trigger the next Ca 2+ -release event (Jiang et al, 2002). In addition, it has been reported that although RyR2 activity decreases when CSQ2 is dissociated (Wei et al, 2009), the relative open probability increases more steeply with luminal Ca 2+ after CSQ2 dissociation (Dulhunty et al, 2012), in agreement with our findings that the rate of spontaneous Ca 2+ release is increased in the absence of CSQ2 (Fig. 3C).…”
Section: Resultssupporting
confidence: 93%
“…95 CASQ2 is part of the RyR2 macromolecular complex which also involves the SR-proteins TRDN and JCTN. 96, 97 . The levels of these proteins are often dramatically altered when CASQ2 is genetically ablated or mutated.…”
Section: Arrhythmias Caused By Heritable Defects In Calcium-handling mentioning
confidence: 99%
“…Indeed junctin-knockout and knockout or mutation of CSQ both increase channel leak and can lead to arrhythmia (Altschafl et al, 2011; Faggioni and Knollmann, 2012). In bilayer studies, experimental removal of CSQ2 from RyR2 increases the sensitivity of RyR2 to changes in luminal Ca 2+ , in a manner that could lead to arrhythmia (Dulhunty et al, 2012). Similar changes in sensitivity to luminal [Ca 2+ ] are seen with junctin knockout (Altschafl et al, 2011) and are likely due to removal of the link to CSQ2.…”
Section: Discussionmentioning
confidence: 99%
“…Inherited or acquired changes in Ca 2+ release lead to skeletal and cardio-myopathies and cardiac death (Györke and Carnes, 2008). The efficacy of Ca 2+ release depends an influence of the ‘Ca 2+ load’ in the SR on the activity of ryanodine receptor (RyR) Ca 2+ release channels, which is facilitated by a Ca 2+ -dependent interaction between CSQ proteins (also known as CASQ) and the RyR through the ‘anchoring’ protein junctin, which is a non-catalytic splice variant encoded by the aspartate-β-hydroxylase ( Asph ) gene (Dulhunty et al, 2009; Dulhunty et al, 2012; Wei et al, 2009a). A second ‘anchoring’ protein, triadin also binds to CSQ and the RyR, but does not transmit signals from CSQ to the RyR in skeletal muscle in vitro (Wei et al, 2009a), although it does influence Ca 2+ release during excitation–contraction coupling in intact myotubes (Goonasekera et al, 2007) and anchoring of CSQ to the junctional SR membrane (Boncompagni et al, 2012).…”
Section: Introductionmentioning
confidence: 99%